2020
DOI: 10.1101/2020.07.02.20145565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Corticosteroids in Non-Intensive Care Unit Patients with COVID-19 Pneumonia from the New York Metropolitan region

Abstract: Introduction: The role of systemic corticosteroid as a therapeutic agent for patients with COVID 19 pneumonia is controversial. Objective: The purpose of this study was to evaluate the effect of corticosteroids in non-intensive care unit (ICU) patients with COVID 19 pneumonia complicated by acute hypoxemic respiratory failure (AHRF). Methods: This was a single-center retrospective cohort study, from the 16th March, 2020 to 30th April, 2020; final follow up on 10th May, 2020. 265 patients consecutively… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…A retrospective cohort study based on propensity score analysis (n = 132 non-severe COVID-19 patients, matching 35 for corticosteroid group-initial MP dosage 40 mg/ d for 8-12 days, and 35 for control group) found that in corticosteroid group, the hospital stay and duration of viral shedding were prolonged, while fever time was shortened, however all these data had no statistically significant differences, and it did not report any adverse effect [90].…”
Section: Implementation Considerationsmentioning
confidence: 99%
“…A retrospective cohort study based on propensity score analysis (n = 132 non-severe COVID-19 patients, matching 35 for corticosteroid group-initial MP dosage 40 mg/ d for 8-12 days, and 35 for control group) found that in corticosteroid group, the hospital stay and duration of viral shedding were prolonged, while fever time was shortened, however all these data had no statistically significant differences, and it did not report any adverse effect [90].…”
Section: Implementation Considerationsmentioning
confidence: 99%
“…In 29 studies the dose of corticosteroids was reported: In 16 studies an equivalent dose of > 1 mg/kg prednisolone was used [37][38][39]41,43,44,[48][49][50][51]53,54,[56][57][58]64] and in 11 studies a lower equivalent dose than 1 mg/kg prednisolone [23,[34][35][36]40,42,47,52,62,63,65]. In two studies a low and high dose group were present [45,46].…”
Section: Corticosteroid Regimen (Table 1 and Appendix 6)mentioning
confidence: 99%
“…In twelve studies length of hospital stay was compared in both corticosteroid and non-corticosteroid groups. The outcomes varied between studies: six reported longer hospital stay in the corticosteroid group [36,47,53,56,66] and ve reported the opposite [23,34,38,52,54] or no effect on hospital stay [58].…”
Section: Effect Of Steroids On Primary and Secondary Outcomes (Table mentioning
confidence: 99%
See 2 more Smart Citations